Intensification treatment based on early FDG‐PET in patients with high‐risk diffuse large B‐cell lymphoma: a phase II GELTAMO trial. (28th July 2014) - Pardal, Emilia; Coronado, Mónica; Martín, Alejandro; Grande, Carlos; Marín‐Niebla, Ana; Panizo, Carlos; Bello, José Luis; Conde, Eulogio; Hernández, Miguel T.; Arranz, Reyes; Bargay, Joan; González‐Barca, Eva; et al.
Summary We conducted a multicentre, phase II study of interim positron emission tomography (PET) as a guide to risk‐adapted therapy in high‐risk patients with newly diagnosed diffuse large B‐cell lymphoma (DLBCL). Patients achieving negative fluorodeoxyglucose (FDG)‐PET after three courses of R‐MegaCHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) received three additional courses, whereas PET‐positive patients received two courses of R‐IFE (rituximab, ifosfamide, etoposide) followed by BEAM (BCNU, etoposide, cytarabine, melphalan) and autologous stem‐cell transplantation. The primary endpoint was progression‐free survival (PFS). 71 patients (median age 55 years, range 25–69) were enrolled. With a median follow‐up of 42·8 months (range 7·2–58·4), the estimated 4‐year PFS and overall survival (OS) were 67% and 78%, respectively, for the global series. Patients in complete remission after interim PET (N = 36) had significantly better 3‐year PFS than those with partial response (N = 30) [81% vs. 57%, Hazard ratio (HR) = 2·6, 95% confidence interval (CI) = 1·02–6·65] but not a statistically significant longer OS. A retrospective PET central review was done for 51 patients. According to semiquantitative analysis, 3‐year PFS (81% vs. 33%; HR = 6·9, 95% CI = 2·35–20·6) and OS (95% vs. 33%, HR = 19·4, 95% CI = 3·89–97·0) were significantly better for negative than for positive interim PET patients. Early PET assessment is valuable for risk stratification in DLBCL; for this purpose semiquantitative evaluation is a better predictor than visual criteria.